2016
DOI: 10.1080/19382014.2016.1162367
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-positive, Glut2-low cells present within mouse pancreas exhibit lineage plasticity and are enriched within extra-islet endocrine cell clusters

Abstract: Regeneration of insulin-producing β-cells from resident pancreas progenitors requires an understanding of both progenitor identity and lineage plasticity. One model suggested that a rare β-cell sub-population within islets demonstrated multi-lineage plasticity. We hypothesized that β-cells from young mice (postnatal day 7, P7) exhibit such plasticity and used a model of islet dedifferentiation toward a ductal epithelial-cell phenotype to test this theory. RIPCre;Z/AP(+/+) mice were used to lineage trace the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 54 publications
6
50
1
1
Order By: Relevance
“…Insulin-expressing Pancreatic Multipotent Progenitor cells (PMPs) were reported that are capable of extensive self-replication, self-renewal and contribute to multiple pancreatic and neural cell types (Smukler et al, 2011). These and similar cells found in small clusters outside of normal islets (Beamish et al, 2016) share a lack of cell-surface Glut2 with the immature beta cells we discovered at the niche. However, the genes enriched in the PMP transcriptome (Razavi et al, 2015) demonstrate virtually no overlap with those enriched in immature beta cells ( Figure S4).…”
Section: Discussionmentioning
confidence: 82%
“…Insulin-expressing Pancreatic Multipotent Progenitor cells (PMPs) were reported that are capable of extensive self-replication, self-renewal and contribute to multiple pancreatic and neural cell types (Smukler et al, 2011). These and similar cells found in small clusters outside of normal islets (Beamish et al, 2016) share a lack of cell-surface Glut2 with the immature beta cells we discovered at the niche. However, the genes enriched in the PMP transcriptome (Razavi et al, 2015) demonstrate virtually no overlap with those enriched in immature beta cells ( Figure S4).…”
Section: Discussionmentioning
confidence: 82%
“…Pancreata were removed for fixation in 4% paraformaldehyde and sectioned for histology as previously described (Beamish et al . ). At least three 7 µm‐thick cryosections (replicates) were cut from each pancreas with an interval between each section >100 µm.…”
Section: Methodsmentioning
confidence: 97%
“…7 Insulin resistance was defined as HOMA-IR >2. 12 Data were expressed as mean ± SEM of variance within islets in each sample. 9 A proinsulin value >10 pmol/L has been reported to be an independent indicator of IR.…”
Section: Introductionmentioning
confidence: 99%